PENGARUH MINUMAN KERAS TERHADAP TINGKAT PERCERAIAN Di KABUPATEN BONE - Nur Hakimah (Al-Maslahah : Jurnal Ilmu Syariah, 2019)
This research aimed to find out and elaborate the influence of alcohol against and to recognize and analyze how tackling the booze against divorce in the Bone Regency. Research methods used an empirical legal research in the disciplines of law to examines the primary data. The data were obtained through observation, interviews, and literature review. The population in this study were judges clerks of the Watampone Religious Court, litigants, and other relevant parties both directly and indirectly participants. The results of this study indicated that the influence of liquor against the Religious Court Watampone in the divorce rate was a substantial influence, because it gave of greatly affects the family economy, damaging mental, strikes the family, and could be isolated from the family its self. As for how to overcome the influence of liquor against divorce in the Bone that it was only formed a regional regulation that specifically, clearly and resolutely set about alcohol.